Alpha-amylase inhibitory activities of ascidians in the treatment of diabetes mellitus - Prabhu, Antonyraj Selva; Ananthan, Gnanakkan (Bangladesh Journal of Pharmacology, 2014)
Extracts of ten selected ascidians with a reputation of usefulness in treating diabetes were examined for alpha-amylase inhibition using an in vitro model. The extract with the highest activity was selected for further characterization. From the results ethyl acetate showed predominant amylase inhibition activity for all species and the maximum level of inhibition was recorded in Phallusia mammillata (68%) at 300 µg/mL and the lowest activity was noted in Microcosmus squamiger (12%) at 200 µg/mL. After preliminary results, the methanolic extract of P. mammallita were further assayed for confirmation of enzyme inhibition and the maximum results (82%) were obtained at 250 µg/mL and the IC50 value of P. mammillata were evidenced at 145.0 ± 0.4 µg/g. In the present study, P. mammillata indicated the maximum ?-amylase activity without toxic effects. Similarly, ?-glucosidase and ?-amylase inhibitor bromophenol, C6H5BrO was produced by P. mammillata.